The social capacity to develop a community. - Zadeh, B. Saheb; Ahmad, Nobaya; Syed Abdul Rashid, Sharifah Norazizan; Abdullah, Haslinda (Maxwell Science Publication, 2010)
The basic purpose of the research is to assess the concept of social capital, community development and relationship that exist between them. A community is constituted by the relationships in which people interact on an everyday basis. In order for people of the same community to have shared norms, values and interests, they need to have the capacity to come together, share, relate, and talk about their norms, values and interests. This capacity is social capital. Social capital is the means by which individual of community interrelate together. Community development is the process by which the efforts of the people themselves are united to improve the quality and quantity of life of the community. The main issue of this paper is “group of people with the high stock of social capital is characterized by trust, norms, values and interests that lead to development of the community and then enable to resolve its problems.” This paper is theoretical in nature and the review is based on secondary materials. Findings show in any community, it is necessary that there be social trust, norms, and networks that people can draw upon to community development to solve their common problems.